Rethinking mathematics learning resources: An interpretative phenomenological study of Indonesian mathematics teachers in digital learning contexts - Nurhikmayati, Iik; Kuncoro, Krida Singgih; Firliani; Sari, Rika Mulyati Mustika (Jurnal Elemen, 2026)
The rapid expansion of digital technology requires mathematics teachers to integrate diverse learning resources effectively; however, existing studies have largely emphasized resource mapping rather than teachers lived experiences and meaning-making. This study addresses this gap by offering a phenomenological perspective on how teachers interpret learning resources in digital contexts. Using a qualitative interpretive paradigm and Interpretative Phenomenological Analysis (IPA), the study explores Indonesian mathematics teachers’ perceptions of resource utilization. Seventy-five teachers from ten cities participated, a sample size methodologically appropriate for IPA. Data were collected through semi-structured open-ended questionnaires and analyzed using IPA procedures. Findings indicate that although teachers increasingly access internet-based resources, textbooks remain the primary instructional reference due to their perceived curricular coherence. Worksheets are considered the most effective resource because they promote structured reasoning, contextual problem-solving, and explicit cognitive engagement, thereby supporting deeper conceptual understanding. These findings align with broader debates in Digital Pedagogy that emphasize pedagogical coherence over technology-driven instruction. Despite ample resources, utilization is constrained by limited digital pedagogical competence and recurring technical challenges. This study contributes by foregrounding teachers’ meaning-making and informing professional development and resource design.